Sensitivity and Specificity of the Mini-Mental State Exam in the Diagnosis of Dementia - L. Sabe; L. Jason; M. Juejati; R. Leiguarda; S. Starkstein (Behavioural Neurology)
The Mini-Mental State Exam (MMSE) is a brief cognitive test that assesses several cognitive domains, such as orientation, attention, concentration, memory, language, and constructional abilities. While the MMSE was found to be valid and reliable in the diagnosis of moderate dementia, its sensitivity and specificity for the diagnosis of mild dementia has been rarely examined. We assessed the specificity and sensitivity of the MMSE in a consecutive series of 44 patients with mild dementia, and a group of age-comparable normal controls. While the specificity of the MMSE for the diagnosis of mild dementia was very high (100%), the sensitivity was only 55% [20 of the 44 patients with mild dementia had an MMSE score in the normal range (≥26 points)]. On the other hand, the assessment with both the Buschke Selective Reminding and the Boston Naming tests discriminated mild Alzheimer's disease patients with normal MMSE scores from controls with a sensitivity and specificity of 64%. In conclusion, the assessment with verbal memory and naming tasks provided a significantly more sensitive measure of early dementia than the MMSE.